Design of a low-quiescent regulator for IoT applications - Chen, Jianyu (Nanyang Technological University, 2023)
With the continuous development of Internet of Things (IoT) technology and the miniaturization of IoT devices, IoT systems are increasingly moving towards the trend of low power consumption and high level of integration. Low dropout (LDO) regulator plays an essential role in the power management chip of IoT applications, so that designing a LDO regulator with high performance has significant practical value. This dissertation proposes an ultra-low quiescent current capacitorless LDO regulator in TSMC 40nm technology. With 1.2V supply voltage, it provides a 1V output voltage and consumes only 854.2nA quiescent current at no load. Through the cascode frequency compensation combining with zero generation and employment of impedance lowering circuit technique, the regulator can operate steadily with a maximum load current of 10mA as well as other load currents in the range. This also gives another benefit for zero minimum load current. Moreover, the regulator exhibits good transient response for the load current to step from 0 to 10mA and vice versa. The simulation results have shown that the overshoot/undershoot voltage and settling time are 15.2mV/94.6mV and 1.05μs, respectively. Overall, it meets the design objectives and is suitable for low power consumption IoT applications.